Biomechanical Testing of Three Alternative Quadrupled Tendon Graft Constructs With Adjustable Loop Suspensory Fixation for Anterior Cruciate Ligament Reconstruction Compared With Four-Strand Grafts Fixed With Screws and Femoral Fixed Loop Devices. Issue 4 (March 2019) - Vertullo, Christopher J.; Piepenbrink, Marina; Smith, Patrick A.; Wilson, Adrian J.; Wijdicks, Coen A.
Background: Quadrupled semitendinosus (ST) grafts for anterior cruciate ligament (ACL) reconstruction have advantages of greater graft diameter and gracilis (G) preservation compared with doubled ST-G grafts. However, a paucity of biomechanical data are available regarding different preparation techniques for these constructs. Purpose: To biomechanically analyze 3 alternative tendon constructs fixed with adjustable suspensory fixation devices on the femur and tibia compared with a matched 4-strand construct fixed with a tibial screw and femoral fixed loop device. Study Design: Controlled laboratory study. Methods: Three alternative quadrupled tendon preparation techniques with suspensory fixation (grafts constructs A, B, and C) were compared with a 4-strand screw-fixed loop device construct (graft construct D) in matched diameter bovine tendon graft and porcine tibia models. Graft constructs were tested with a 3-stage cyclic loading protocol (1000 cycles in position control and 1000 cycles each from 10 to 250 N and from 10 to 400 N), followed by a pull to failure. In graft construct A, the graft ends were whipstitched and tied over the tibial button; in graft construct B, the graft ends functioned as pulleys; and in graft construct C, a continuous loop was created. Initial, dynamic, and total elongation, stiffness, and ultimate failure load were recorded. Results: Graft construct D had the highest initial (0.51 ± 0.29 mm) and total (3.53 ± 0.98 mm) elongation compared with the 3 quadrupled constructs ( P < .001 each). Graft construct B had lower total elongation (2.13 ± 0.31 mm) compared with graft construct A (2.40 ± 0.30 mm) ( P = .004) and graft construct C (2.53 ± 0.21 mm) ( P = .007). Graft construct C had a higher ultimate failure load (1097 ± 79 N) compared with graft construct A (988 ± 112 N) ( P = .001), graft construct B (973 ± 137 N) ( P = .022), and graft construct D, which had the lowest failure load (767 ± 182 N) ( P < .001). Conclusion: The 3 quadrupled tendon suspensory fixation constructs exhibited small yet statistically significant biomechanical differences among each other. Constructs that used tibial screw fixation had lower ultimate failure load and higher total elongation compared with the quadrupled tendon constructs. Clinical Relevance: Total elongation for the screw fixation group was higher than the threshold of clinical failure, which may allow for graft construct elongation during the postoperative rehabilitation phase. Biomechanical properties of the 3 quadrupled tendon suspensory graft constructs may be clinically comparable, albeit statistically different.